Should Patients with Hepatic Fibrosis Undergo LVAD Implantation: A Comparative Analysis. Issue 4 (July 2016) - Xuereb, Linnea; Go, Pauline H.; Kaur, Babbaljeet; Akrawe, Silvy; Borgi, Jamil; Paone, Gaetano; Morgan, Jeffrey A.
Abstract : The purpose of our study was to evaluate outcomes in patients with hepatic fibrosis at the time of LVAD implantation. There were five (2.1%) patients with preoperative hepatic fibrosis with a mean age of 51.2 ± 16.8 years. Survival at 180 days was significantly reduced in patients with hepatic fibrosis, 40.0% vs. 88.0%; p = 0.001. Hepatic fibrosis was a significant independent predictor of mortality in multivariate analysis (hazard ratio [HR] 2.27, p = 0.036).